Mengungkap Hubungan Sikap Kerja Karyawan Terhadap Kinerja Melalui Variabel Mediasi Employee Engagement (Jurnal Simki Economic, 2023)
The objective of this study is to evaluate how much influence work attitude has on performance, both partially and simultaneously. The basis for analyzing data using SEM-PLS as a calculating tool to analyze the outer and inner models is quantitative methods and correlational designs. Purposive sampling generated a total of 73 respondents. The outcome is that 1) work attitude, precisely employee craftsmanship, has a significant effect on employee engagement; 2) employee engagement, precisely employees feeling comfortable developing a career, has a substantial effect on performance; 3) work attitude, precisely employee craftsmanship, has a substantial effect on performance; and 4) work attitude has a moderate effect on performance through employee engagement. The novelty is employees who are diligent (work attitude), comfortable developing careers (employee engagement), and leaders who appreciate work (performance) are alternative offers to optimize employee capabilities in the workplace.